Has the "external constraint" contributed to Italy's stagnation? A critical event analysis - Lucio Baccaro; Massimo D'Antoni (Max Planck Institute for the Study of Societies, 2020)
Has the strategy of the "external constraint" (voluntarily limiting the country's policy-making discretion by tying it to the European mast) contributed to Italy's stagnation over the past twenty-five years? The existing literature is divided on this question. The dominant interpretation is that Italy's stagnation is due to insufficient liberalization, and that the external constraint has had no negative and even a positive influence. An alternative interpretation emphasizes the demand compression and supply-side effects of the external constraint. Based on three case studies of public debt management, privatization, and labor market policy, this paper reconstructs the process by which the external constraint has affected outcomes. It argues that it has had a negative impact, but more as a necessary condition than as a sufficient one. In other words, it would probably have been possible to manage the external constraint differently to produce better outcomes, but without the external constraint, the stagnation would likely have been less deep. – – Hat die Strategie des "äußeren Zwangs" (die freiwillige Einschränkung der politischen Gestaltungsmacht eines Landes durch seine Unterwerfung unter europäische Vorgaben) zu Italiens Stagnation in den letzten 25 Jahren beigetragen? Die vorliegende Literatur ist in dieser Frage zwiegespalten. Die vorherrschende Deutung besagt, dass Italiens Stagnation einer unzureichenden Liberalisierung geschuldet ist und der äußere Zwang keinen negativen, sondern im Gegenteil einen positiven Einfluss gehabt hat. Eine alternative Interpretation verweist jedoch auf die einbrechende Nachfrage und die Angebotseffekte, die der äußere Zwang verursacht. Auf der Grundlage dreier Fallstudien zum öffentlichen Schuldenwesen, zur Privatisierung und zur Arbeitsmarktpolitik rekonstruiert dieser Beitrag den Prozess, durch den der äußere Zwang Resultate beeinflusst hat. Er vertritt die These, dass dieser Zwang zwar einen negativen Einfluss ausgeübt hat, dies jedoch eher als notwendige denn als hinreichende Bedingung. Es wäre, anders ausgedrückt, also wahrscheinlich möglich gewesen, anders mit dem äußeren Zwang umzugehen, und zwar so, dass bessere Resultate erzielt worden wären; ohne diesen Zwang wäre die Stagnation allerdings wohl weniger einschneidend verlaufen.
hdl:21.11116/0000-0006-B77E-F
Keywords: 300; economic decline; euro; Italy; political economy; Italien; politische Ökonomie; wirtschaftlicher Niedergang